Allmänhetens syn på våldsbejakande extremism: En balans mellan sociala, ekonomiska och polisiära åtgärder - Lars Korsell; Tomas Axelson; Jonas Stier (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The so-called Swedish model of trust is characterised by strong public support for the idea of an individual-based and extensive welfare state, well-developed state individualism, high levels of social trust, widespread appreciation of the judiciary, openness, tolerance, and a free and independent press. Today, Swedish society faces several challenges. Will the Swedish model of trust be eroded or is it relatively resilient to stress?